REKAYASA SISTEM INFORMASI PROMOSI DAN PENGELOLAAN JASA STUDIO FOTO BERBASIS WEB - Rosdiana Rosdiana; Denny Kurniadi; Asrul Huda (Universitas Negeri Padang, 2019)
The information system appear give support and advantages in all areas of life. One of them is on economic. Photo studio is a part of economic field. Photo studio that offer photography and video recording service have a broad target market. Photo studio still use manual system and have not utilized the information system optimally in promote and manage it system that can causes many problems. For example, the problem in inform service packages, problem in booking that has impact to report. The purpose of information system is to minimize mistakes and optimize the promotion that offer by provider photograph services (photo studio, photographer and freelance videographer). Show detail information such as : portfolio and art gallery. So, customers can order easily. Information system also can give order report in periodic time for provider services. Information systems designed by waterfall method. Developed with php language, laravel framework and Mysql database.Keywords : Information systems, Photo Studio, Management, Laravel Framework.